Curriculum Design for Technical Training in Public Transportation Management at the BPSDM of West Java Province (Universitas Pendidikan Indonesia (UPI), 2025)
The development of the competency of State Civil Apparatus (ASN) through training programs is an important strategy in improving the quality of public services. This study aims to analyze the problems and design a curriculum update for the Public Transportation Management Technical Training at the BPSDM of West Java Province using the Tyler (2013) curriculum model which includes the formulation of objectives, selection of learning methods, preparation of materials, and evaluation. The research method used is descriptive qualitative through interviews and document reviews, with informants consisting of heads of divisions, training organizers, instructors, and training participants. Data analysis was carried out through the stages of reduction, presentation, and drawing conclusions. The results of the study identified three main problems: (1) the training was not based on needs analysis so that the curriculum did not fully reflect the competency gaps of participants, (2) the curriculum structure still emphasized the knowledge aspect with limited learning methods and minimal practice, and (3) the evaluation only measured the cognitive aspect through pre-tests and post-tests without assessing applicative skills. The alternative curriculum design was carried out by referring to the Tyler model, including the formulation of clearer learning objectives, the preparation of materials based on the needs of participants, the application of varied learning methods, and evaluation based on learning levels through mini projects or implementation tasks. This study recommends that the resulting curriculum design can be used as a reference in organizing training, with an emphasis on analyzing specific competencies according to job groups and strengthening implementation-based evaluation to increase the relevance and usefulness of training results .